PENDAMPINGAN PENGUATAN DAYA TARIK WISATA DESA TOWALE - Sutomo, Maskuri; Samudra, Suryadi; Asngadi; Tambaru, Rahman; Palawa, Muhammad Riswandi (Abdimas Awang Long, 2024)
This community service activity aims to provide strengthening and understanding of the importance of tourism villages for the community in Towale Village, Donggala Regency. In 2023, Towale Village was selected to be included in the top 75 national tourist villages at the Anugrah Desa Wisata (ADWI) organized by the Ministry of Tourism and Creative Economy (Kemenparekraf). The research methodology involved active collaboration with local stakeholders, including the village government, local entrepreneurs and the local community. The main steps included identification of existing tourism resources, SWOT analysis, and joint strategic planning to develop sustainable tourism attractions as well as monitoring and evaluation on program implementation.The results showed great potential in developing various aspects of the tourist attraction, including natural beauty, cultural heritage, and local experiences. Through various activities, such as tourism management training, local promotion, and infrastructure development, this assistance encourages various initiatives aimed at improving the quality of the tourist experience.